WOLFGANG BORCHERT'S SHORT STORY IN TEACHING GERMAN LANGUAGE - Nikolina N. Zobenica (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2011)
In teaching a foreign language the literature takes a marginalized role. If it receives some attention, there are only extracts worked on and the literary work is being treated as any other text, without its particularities coming to expression. However, working on a literary text in classes of a foreign language offers a number of opportunities, from acquiring linguistic, literary and cultural knowledge through developing various competences to affecting the personality of young people. In this paper there will be advanced the arguments for implementation of Wolfgang Borchert's short story in teaching German language, given a model for working on the short story and discussed the merit of such a text approach, with the aim to encourage introducing literature in teaching foreign languages in higher classes of grammar schools and at the universities.